2017
DOI: 10.1002/pbc.26711
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the effectiveness of the neutropenic diet versus food safety guidelines on infection rate in pediatric oncology patients

Abstract: Background: The neutropenic diet (ND) is prescribed to avoid introduction of bacteria into a host's gastrointestinal tract and reduce infection. Due to a lack of evidence to support the ND, there continues to be debate among pediatric oncologists regarding its usefulness. This prospective randomized controlled trial evaluated the difference in neutropenic infection rates in pediatric oncology patients randomized to Food and Drug Administration approved food safety guidelines (FSGs) versus the ND plus FSGs duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 31 publications
(34 reference statements)
1
65
0
2
Order By: Relevance
“…A study involving 153 patients receiving chemotherapy for acute myeloid leukemia or myelodysplastic syndrome randomized 78 patients to a diet that restricted raw fruits and vegetables and 75 patients to a diet that included those foods. 8 The groups had similar rates of major infection (29% in the cooked group versus 35% in the raw group, P = .60) with no difference in mortality. 7 In a randomized, multi-institutional trial of 150 pediatric oncology patients, 77 patients received a neutropenic diet plus a diet based on the food safety guidelines approved by the Food and Drug Administration (FDA), while 73 children received a diet based on FDA-approved food safety guidelines.…”
Section: Why the Neutropenic Diet Is Not Helpful In Preventing Infectionmentioning
confidence: 84%
See 2 more Smart Citations
“…A study involving 153 patients receiving chemotherapy for acute myeloid leukemia or myelodysplastic syndrome randomized 78 patients to a diet that restricted raw fruits and vegetables and 75 patients to a diet that included those foods. 8 The groups had similar rates of major infection (29% in the cooked group versus 35% in the raw group, P = .60) with no difference in mortality. 7 In a randomized, multi-institutional trial of 150 pediatric oncology patients, 77 patients received a neutropenic diet plus a diet based on the food safety guidelines approved by the Food and Drug Administration (FDA), while 73 children received a diet based on FDA-approved food safety guidelines.…”
Section: Why the Neutropenic Diet Is Not Helpful In Preventing Infectionmentioning
confidence: 84%
“…14 Patients and family members reported that following the neutropenic diet requires considerably more effort than following a less restrictive diet. 8 Maintaining nutrition in this patient population is already challenging, and the restriction of a wide variety of food items (fresh fruits, vegetables, dairy, certain meats, eggs) can cause malnutrition, low patient satisfaction, and poor quality of life. 13,14 WHEN MIGHT THE NEUTROPENIC DIET BE HELPFUL?…”
Section: Why the Neutropenic Diet Is Not Helpful In Preventing Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the scientific support for the neutropenic diet is largely empirical, adherence to these diets is difficult and provides further restraints on the individual's dietary intake. 13 Most importantly, clinical trials have not found this diet to be effective in the prevention of infection over and above that of food safety guidelines. [13][14][15] It is plausible that incorporating foods and supplements high in pre-or probiotics may be safe and beneficial within the context of childhood cancer; however, additional research is needed.…”
Section: Neutropenic Diet/low Microbial Dietmentioning
confidence: 99%
“…13 Most importantly, clinical trials have not found this diet to be effective in the prevention of infection over and above that of food safety guidelines. [13][14][15] It is plausible that incorporating foods and supplements high in pre-or probiotics may be safe and beneficial within the context of childhood cancer; however, additional research is needed. It is essential that dietary counseling within integrative oncology adheres to food safety guidelines to reduce the risk of food-borne illnesses.…”
Section: Neutropenic Diet/low Microbial Dietmentioning
confidence: 99%